Varicella Infection Complicated by Group A Beta-Hemolytic Streptococcal Retropharyngeal Abscess - Christine M. Clark; Colin Huntley; Michele M. Carr (Case Reports in Otolaryngology)
An unimmunized 19-month-old child presented with a retropharyngeal abscess and coincident varicella infection. The abscess resolved with operative drainage. This is the first published report of this connection, although varicella is known to be associated with abscesses in general. Practitioners should be aware that cervical abscesses may complicate varicella infections.